A YAP/TAZ-TEAD signalling module links endothelial nutrient acquisition to angiogenic growth - Ong, Yu Ting (2022)
Funding Information: The research in the M.P. laboratory was supported by the Max Planck Society, the European Research Council (ERC) Consolidator Grant EMERGE (no. 773047), the Deutsche Forschungsgemeinschaft (DFG, Project-ID 75732319 – SFB 834), the Leducq Foundation, the European Union’s Horizon 2020 research and innovation programme under the Marie Sklodowska-Curie action (no. 814316), the Excellence Cluster Cardio-Pulmonary Institute (EXC 2026, Project-ID 390649896), the DZHK (German Centre for Cardiovascular Research), the Stiftung Charité and the European Molecular Biology Organization (EMBO) Young Investigator Programme. Work in the H.G. laboratory was supported by the DFG, Project-ID 427826188 – SFB 1444 and Project-ID 437531118 – SFB1470. Research in the Carmeliet laboratory is supported by Methusalem funding by the Flemish government and by an ERC Advanced Research grant (no. EU-ERC269073). This work was performed with assistance from the CSHL Mass Spectrometry Shared Resource, which is supported by a Cancer Centre Support grant (no. 5P30CA045508). Publisher Copyright: © 2022, The Author(s).